القيمة الاقتصادية المضافة كنموذج فعال لتقييم الأداء المالي للمؤسسات الاقتصادية. دراسة حالة: مؤسسة Algal Plus بالمسيلة. - بوزربة, رشيد; يحياوي, سمير (جامعة الوادي - University of Eloued, 2021)
This study aims at determining the extent of the ability of the Economic Value Added Index in assessing the financial performance of economic institutions from an economic perspective, which is concerned as a comprehensive and integrated approach. Moreover, it deems to determine its high capacity in linking the operating profit of the institution with the Wacc. Additionally, The study was based on the descriptive approach which is appropriate for the study objectives of the study through an accurate description of the phenomenon studied. The study concluded that there is a process of value demolition that the institution’s inability to create wealth for shareholders, Considering that the latter is one of the strategic goals that the financial management seeks to achieve.
Economic value added as an effective model for evaluating the financial performance economic institutions. CASE STUDY ALGAL PLUS institution -M’sila.
مقال
Keywords: الأداء المالي ; القيمة الاقتصادية المضافة ; تكلفة رأس المال